1996
DOI: 10.1093/infdis/173.3.669
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction-Based Sequence-Specific Oligonucleotide Hybridization Analysis of HLA Class II Antigens in Pulmonary Tuberculosis: Relevance to Chemotherapy and Disease Severity

Abstract: HLA antigens were studied by serology and polymerase chain reaction-based sequence-specific oligonucleotide hybridization techniques in 153 patients with pulmonary tuberculosis (PTB) and 289 healthy controls. HLA-DR2 was present more frequently in PTB patients than in controls (51% vs. 36.3%; corrected P[Pc]=.029, relative risk [RR] = 1.8). The DR2 association was stronger in patients in the drug-failure group (n=56; Pc=.000012, RR=3.7) than in healthy controls and in patients in the drug-responder group. No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 32 publications
2
43
0
1
Order By: Relevance
“…For example, DRB1*15 has been reported to be associated with the susceptibility of TB in various ethnic groups such as Indian (Rajalingam et al, 1996;Ravikumar et al, 1999;Stroup DF et al, 2000;Sriram et al, 2001;Mishra et al, 2014;Kuranov et al, 2014), Mexican (Teran et al, 1999), Chinese (Shi et al, 2011), Polish (Dubaniewicz et al, 2005) and Korean (Kim et al, 2005). DRB1*16 is reported to have a positive association with the susceptibility to tuberculosis in Polish population (Dubaniewicz et al, 2005), but a negative association in the Sahariya tribe of North Central India (Mishra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, DRB1*15 has been reported to be associated with the susceptibility of TB in various ethnic groups such as Indian (Rajalingam et al, 1996;Ravikumar et al, 1999;Stroup DF et al, 2000;Sriram et al, 2001;Mishra et al, 2014;Kuranov et al, 2014), Mexican (Teran et al, 1999), Chinese (Shi et al, 2011), Polish (Dubaniewicz et al, 2005) and Korean (Kim et al, 2005). DRB1*16 is reported to have a positive association with the susceptibility to tuberculosis in Polish population (Dubaniewicz et al, 2005), but a negative association in the Sahariya tribe of North Central India (Mishra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For isoniazid, a widely used antituberculosis medication, slow acetylators are at increased risk of developing peripheral neuropathy (41), while rapid acetylators, who quickly clear the drug, are at increased risk of treatment failure (127) and possibly developing drug-resistant variants. HLA-DR2 was also found to be associated with drug resistance in one study (102).…”
Section: Antimicrobial Agents/pharmacogeneticsmentioning
confidence: 93%
“…111 Thus, several studies of HLA association with pulmonary tuberculosis have been carried out in Chinese, 111,112 Korean, 113 Indonesian, 114 Indian 115-121 and Russian patients. 122 Of the numerous Indian studies on HLA association with pulmonary tuberculosis, the earlier studies focussed on association of HLA Class I antigens 115,116 and later in family studies in North India 118,120 and South India 117,121 that focussed on HLA Class II antigens. An increased frequency of HLA-DR2 and DQ1 was shown to be associated with the susceptibility to pulmonary tuberculosis in Indian population.…”
Section: Hla and Mycobacterium Tuberculosis Infectionmentioning
confidence: 99%
“…Molecular study has revealed that the allele DRB1*1501 of HLA-DR2 was higher compared with DRB1*1502 in North Indian patients. [117][118][119][120][121]123 Moreover, the TAP2 has been found associated with active tuberculosis along with HLA-DR2 in North Indian pulmonary tuberculosis patients.…”
Section: Hla and Mycobacterium Tuberculosis Infectionmentioning
confidence: 99%